Evaluating the efficacy and safety of transcranial pulse stimulation on adolescents with attention deficit hyperactivity disorder: Study protocol of a pilot randomized, double-blind, sham-controlled trial - Cheung, Teris; Chau, Bolton; Fong, Kwan Hin; Lam, Joyce Yuen Ting; Lo, Herman; Li, Man Ho; Li, Albert Martin Man Chim; Beisteiner, Roland; Lei, Sun; Yee, Benjamin K.; Cheng, Calvin Pak Wing (Frontiers in Neurology, 2023)
Background Traditional treatment alone might not effectively control the severity of attention deficit hyperactivity disorder (ADHD) symptoms. Transcranial pulse stimulation (TPS) is a non-invasive brain stimulation (NIBS) technology used on older adults with mild neurocognitive disorders and adults with major depressive disorder. However, there has been no study conducted on young adolescents with ADHD. This will be the first nationwide study evaluating the efficacy and safety of TPS in the treatment of ADHD among young adolescents in Hong Kong. Methods This study proposes a double-blinded, randomized, sham-controlled trial including TPS as an intervention group and a sham TPS group. Both groups will be measured at baseline (T1), immediately after the intervention (T2), and at the 1-month (T3) and 3-month follow-ups (T4). Recruitment A total of 30 subjects aged between 12 and 17 years, diagnosed with attention deficit hyperactivity disorder (ADHD), will be recruited in this study. All subjects will be computer randomized into either the intervention group or the sham TPS group on a 1:1 ratio. Intervention All subjects in each group will have to undertake functional MRI (fMRI) before and after six 30-min TPS sessions, which will be completed in 2 weeks' time. Outcomes Baseline measurements and post-TPS evaluation of the ADHD symptoms and executive functions will also be conducted on all participants. The 1- and 3-month follow-up periods will be used to assess the long-term sustainability of the TPS intervention. For statistical analysis, ANOVA with repeated measures will be used to analyze data. Missing data were managed by multiple imputations. The level of significance will be set to p < 0.05. Significance of the study Results emerging from this study will generate new knowledge to ascertain whether TPS can be used as a top-on treatment for ADHD. Clinical trial registration clinicaltrails.gov, identifier: NCT05422274.